Effect of Bocce Game on Perceptual Motor Ability and Object Control among Adolescents with Mental Retardation - Badruzaman, B (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The study investigated the effect of the Bocce game on developing perceptual-motor ability and object control of adolescents with mental retardation. The subjects of the research were 15 adolescents with moderate Mental Retardation status (Age =16.4±1.59; IQ 54±.5). The study used a quasi-experimental method with a one-group pre-test post-test design. The analysis was conducted by using a T-test. The instrument used in this study was an observation employing an observation checklist adapted from Gallahue’s (1982) assessment checklist to measure perceptual-motor ability. A test was also employed to measure object control, including an underhand roll ball (grounder) test on the target using a Bocce ball with a 4-meter distance. The intervention of Bocce Game was given for 12 sessions. Each session lasted for 2 hours, 3 days per week. The statistical analysis showed the significant effect of the Bocce game on developing perceptual-motor ability (2.73 2.145) and object control (22.85 2.145). For that reason, it concludes that there is a significant effect of the Bocce game on perceptual-motor ability and object control of adolescents with mental retardation.